Scaling a software business : the digitalization journey (2017)
This book is a product of a research project that tackled one of the key challenges currently facing the software industry in Europe, and indeed worldwide, namely, how do we transform our organization as software increasingly becomes a critical part of our business? How can we support the digitalization of assets and offerings? This book presents the Scaling Management Framework (SMF), which is unique in the sense that it supports the above transformation in three domains: 1) products systems & services, 2) organization & business, and 3) methods & processes. These domains are interdependent and are integrated into a single model in the SMF.